A search for R-parity-violating supersymmetry in final states containing many jets in pp collisions at s = 13 TeV with the ATLAS detector - Aad, G; Abbott, B; Abeling, K; Abicht, NJ; Abidi, SH; Aboulhorma, A; Abramowicz, H; Abreu, H; Abulaiti, Y; Acharya, BS; Adam Bourdarios, C; Adamczyk, L; et al. (Springer, 2024)
A search for R-parity-violating supersymmetry in final states with high jet multiplicity is presented. The search uses 140 fb−1 of proton-proton collision data at s = 13 TeV collected by the ATLAS experiment during Run 2 of the Large Hadron Collider. The results are interpreted in the context of R-parity-violating supersymmetry models that feature prompt gluino-pair production decaying directly to three jets each or decaying to two jets and a neutralino which subsequently decays promptly to three jets. No significant excess over the Standard Model expectation is observed and exclusion limits at the 95% confidence level are extracted. Gluinos with masses up to 1800 GeV are excluded when decaying directly to three jets. In the cascade scenario, gluinos with masses up to 2340 GeV are excluded for a neutralino with mass up to 1250 GeV.